The Influence of Regional Taxes, Regional Levies, Profit Sharing Funds, and General Allocation Funds on Regional Spending (Case Study of Regency and Municipality in Central Java) - Dhevianti, Maria; Aresteria, Maya (Politeknik Negeri Ambon, 2024)
The background of the problem in this study is that the realization of Regional Levies revenues, Profit Sharing Funds and General Allocation Funds in Semarang Regency is not in accordance with the budgeted so that Regional Expenditure has decreased. This study aims to determine whether Regional Taxes, Regional Levies, Profit Sharing Funds, and General Allocation Funds affect Regional Expenditures. The population and sample of this study are regencies and municipalities in Central Java. Regional spending has an important role in running the government system, namely to improve public welfare and as a form of good governance. This study uses multiple linear regression analysis using data obtained from a summary of the 2020 and 2021 Regional Budget (APBD) realization reports which are quantitative published on the Indonesia Statistics. The number of samples in this study are 70. The results of the study show that Regional Taxes and General Allocation Funds have a positive effect on Regional Expenditure, while Regional Levies and Profit Sharing Funds have no effect on Regional Expenditure.